Role of assessment components and recent adverse outcomes in risk estimation and prediction: Use of the Short Term Assessment of Risk and Treatability (START) in an adult secure inpatient mental health service. (30th June 2016) - O'Shea, Laura E.; Dickens, Geoffrey L.
Abstract: The Short Term Assessment of Risk and Treatability is a structured judgement tool used to inform risk estimation for multiple adverse outcomes. In research, risk estimates outperform the tool's strength and vulnerability scales for violence prediction. Little is known about what its'component parts contribute to the assignment of risk estimates and how those estimates fare in prediction of non-violent adverse outcomes compared with the structured components. START assessment and outcomes data from a secure mental health service ( N= 84) was collected. Binomial and multinomial regression analyses determined the contribution of selected elements of the START structured domain and recent adverse risk events to risk estimates and outcomes prediction for violence, self-harm/suicidality, victimisation, and self-neglect. START vulnerabilities and lifetime history of violence, predicted the violence risk estimate; self-harm and victimisation estimates were predicted only by corresponding recent adverse events. Recent adverse events uniquely predicted all corresponding outcomes, with the exception of self-neglect which was predicted by the strength scale. Only for victimisation did the risk estimate outperform prediction based on the START components and recent adverse events. In the absence of recent corresponding risk behaviour, restrictions imposed on the basis of START-informed risk estimates could be unwarranted and may be unethical. Highlights: The START aims to assist formulation of short-term risk based on multiple factors. Recent corresponding adverse events was the best predictor for all outcomes studied. Additional predictive value was not added by START components. Prediction of self-harm and victimisation was improved by raters' risk estimate. Risk management restrictions based on START formulation might be unwarranted.